A flexible carbon nanotube conductive hollow fiber membrane and a large-scale preparation method thereof

Through cross-linking of silane coupling agent and polyvinyl butyral and wet spinning technology, carbon nanotube hollow fiber membranes with high flexibility and conductivity were prepared, solving the fragility and insufficient conductivity of the existing films. The problem is suitable for the treatment of high water pressure and negative electrical pollutants.

CN115920666BActive Publication Date: 2025-01-03DALIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211436309.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-16
Publication Date
2025-01-03
Estimated Expiration
2042-11-16

AI Technical Summary

Technical Problem

The membrane of existing carbon nanotube hollow fibers is brittle and easy to break, has poor flexibility, and has poor electrical conductivity, which cannot meet the actual application needs.

Method used

The flexible carbon nanotube conductive hollow fiber membrane was prepared by cross-linking with polyvinyl butyral and carbon nanotubes by wet spinning process. The carbon nanotubes were stably dispersed and pores were formed by polyvinylpyrrolidone. Hollow fiber membrane structure.

Benefits of technology

It improves the tensile strength, flexibility and conductivity of the hollow fiber membrane of carbon nanotubes, and can not rupture under high water pressure. It is suitable for water treatment of negative electrical pollutants, reducing energy consumption and improving anti-pollution performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115920666B_ABST
    Figure CN115920666B_ABST
Patent Text Reader

Abstract

The invention discloses a flexible carbon nanotube conductive hollow fiber membrane and a large-scale preparation method thereof. The large-scale preparation method of the flexible carbon nanotube conductive hollow fiber membrane comprises the following steps: firstly, polyvinyl pyrrolidone, carbon nanotubes, polyvinyl butyral and silane coupling agent are dispersed in an organic solvent by ultrasonic stirring at a certain mass ratio, and then, after standing and degassing, a spinning solution is obtained; and then, the spinning solution and water are extruded into a water coagulation bath through a spinning head at a certain flow ratio to obtain a carbon nanotube hollow fiber membrane. The preparation method is safe, simple and efficient, and does not require expensive chemical reagents and equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of membrane technology, and particularly relates to a flexible carbon nanotube conductive hollow fiber membrane and a large-scale preparation method thereof. Background Art

[0002] Membrane separation technology has the advantages of small footprint, high separation efficiency, easy modularization and automation, and is widely used in environmental protection, petrochemical, food, medical and seawater desalination. Among the many types of separation membranes, hollow fiber membranes have large specific surface area, high filling density and simple preparation methods. They have been widely used in the field of water treatment, bringing significant environmental and economic effects and have broad development prospects.

[0003] Patent CN104028112B reports a carbon nanotube hollow fiber membrane with high porosity, high pure water flux and good electrical conductivity. It can be coupled with electrochemistry to further improve its interception performance and anti-pollution ability through electrostatic repulsion, electrical adsorption and electrochemical oxidation-reduction, showing advantages that traditional separation membranes do not have. However, the prepared carbon nanotube hollow fiber membrane is brittle and easy to break, has poor flexibility and poor electrical conductivity, and cannot meet the needs of practical applications. Therefore, it is of great value and significance to develop a carbon nanotube hollow fiber membrane with structural flexibility and good electrical conductivity and a large-scale preparation method. Summary of the invention

[0004] The present invention mainly aims at the problems that the existing self-supporting carbon nanotube hollow fiber membranes are brittle and easy to break, have low flexibility and poor conductivity, that is, their tensile strength, bending strength and conductivity need to be further improved, and provides a flexible carbon nanotube conductive hollow fiber membrane and a large-scale preparation method thereof.

[0005] The first aspect of the present invention provides a flexible carbon nanotube conductive hollow fiber membrane, which contains a silane coupling agent, polyvinyl butyral, polyvinyl pyrrolidone and carbon nanotubes, and the mass ratio of the polyvinyl pyrrolidone, the carbon nanotubes, the polyvinyl butyral and the silane coupling agent is 0.2-1:1:0.15-0.5:0.05-0.5; the carbon nanotubes and the polyvinyl butyral are cross-linked by the silane coupling agent.

[0006] Furthermore, in the above technical solution, the silane coupling agent includes one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane, N-β-aminoethyl-γ-aminopropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and vinyl-tri(2-methoxyethoxy)silane, preferably γ-aminopropyltriethoxysilane.

[0007] Furthermore, in the above technical solution, the molecular weight of the polyvinyl pyrrolidone is 8000-1300000, preferably 40000-58000; the molecular weight of the polyvinyl butyral is 25000-2000000, preferably 170000-250000.

[0008] Furthermore, in the above technical solution, the carbon nanotubes include one or more of carboxylated multi-walled carbon nanotubes, hydroxylated multi-walled carbon nanotubes, and single-walled carbon nanotubes.

[0009] The second aspect of the present invention provides a large-scale preparation method of a flexible carbon nanotube conductive hollow fiber membrane, comprising the following steps:

[0010] (1) dispersing polyvinyl pyrrolidone, carbon nanotubes, polyvinyl butyral and a silane coupling agent in an organic solvent at a temperature of 30 to 60° C., stirring evenly and then standing to degas to obtain a spinning solution;

[0011] (2) Wet spinning: The spinning solution is used as the shell liquid and water is used as the core liquid. The spinning solution and the core liquid are extruded into a water coagulation bath through a spinning head at a volume flow ratio of 1 to 3:1. The obtained product is soaked, washed and then dried.

[0012] Furthermore, in the above technical solution, the organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

[0013] Furthermore, in the above technical solution, the drying includes drying at room temperature or drying at a temperature not higher than 100°C.

[0014] The third aspect of the present invention provides the use of the above-mentioned flexible carbon nanotube conductive hollow fiber membrane or the flexible carbon nanotube conductive hollow fiber membrane prepared by the above-mentioned preparation method, which is applied to the treatment of water with negatively charged pollutants.

[0015] Furthermore, in the above technical solution, the water treatment with negatively charged pollutants includes industrial wastewater treatment or drinking water purification.

[0016] Furthermore, in the above technical solution, it is applied to closed containers or immersed vacuum filtration water treatment with large hydraulic scouring or turbulent water flow, and can withstand at least 2Mpa of water pressure without breaking.

[0017] In the field of water treatment, since most pollutants are negatively charged, the prepared carbon nanotube hollow fiber membrane has good conductivity. Therefore, after applying a small negative voltage to the membrane, the electrostatic repulsion generated between the membrane and the pollutants can reduce the deposition of pollutants on the membrane surface. Due to the good conductivity and small applied voltage, energy consumption is greatly reduced. It can also be used with other electrochemical oxidation-reduction, electrowetting, electrobubbling, etc. produced by coupling conductive membranes with electrochemical technologies to achieve the anti-pollution performance of the membrane.

[0018] The basic concept of the present invention is:

[0019] (1) The silane coupling agent's silaneoxy group and organic functional group react with carboxylated or hydroxylated carbon nanotubes and polyvinyl butyral, respectively, acting as a molecular bridge to form a "polyvinyl butyral-silane coupling agent-carboxylated multi-walled carbon nanotube" bonding layer, connecting the carbon nanotubes and the polymer together, increasing the bonding strength between the carbon nanotubes, and thus improving the flexibility of the carbon nanotube hollow fiber membrane.

[0020] (2) In the wet spinning process, the carbon nanotubes are cross-linked by utilizing the instant solidification of polyvinyl butyral when the casting solution contacts the water coagulation bath to form a hollow fiber membrane structure. The role of polyvinyl pyrrolidone is to stably disperse the carboxylated or hydroxylated carbon nanotubes and to act as a porogen in the non-solvent induced phase transformation.

[0021] The beneficial effects of the present invention are:

[0022] (1) The carbon nanotube hollow fiber membrane of the present invention has high tensile strength, large tensile breaking energy, good flexibility, and can be bent and twisted.

[0023] (2) The carbon nanotube hollow fiber membrane described in the present invention has good electrical conductivity.

[0024] (3) The method for preparing the carbon nanotube hollow fiber membrane of the present invention is safe and simple, has a short cycle, and does not require expensive chemical reagents and equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0026] Figure 1 The outer surface of the carbon nanotube hollow fiber membrane prepared in Example 4 is imaged at 30 times (A) and 50,000 times (B) by scanning electron microscope.

[0027] Figure 2 This is a 130x scanning electron microscope image of the cross section of the carbon nanotube hollow fiber membrane prepared in Example 4.

[0028] Figure 3 This is a scanning electron microscope image of the cross section of the carbon nanotube hollow fiber membrane prepared in Example 4 at 10,000 times magnification.

[0029] Figure 4 This is a photograph of the carbon nanotube hollow fiber membrane prepared in Example 4 being twisted and bent.

[0030] Figure 5 These are photos of the flexibility test of the carbon nanotube hollow fiber membrane prepared in Example 5, where A is a photo of the diameter of the shaft rod; B is a photo of the carbon nanotube hollow fiber membrane bent and wrapped around the shaft rod; C is a photo of the carbon nanotube hollow fiber membrane being pulled away from the shaft rod; and D is a photo of the carbon nanotube hollow fiber membrane returning to its initial state.

[0031] Figure 6 These are photos of the conductivity test of the carbon nanotube hollow fiber membrane prepared in Example 5, where A is a photo of the resistance test of the carbon nanotube hollow fiber membrane in a dry state; and B is a photo of the resistance test of the carbon nanotube hollow fiber membrane in a wet state immersed in water. DETAILED DESCRIPTION

[0032] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with specific examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0033] Example 1

[0034] (1) Preparation of spinning solution: The mass ratio of polyvinyl pyrrolidone, carbon nanotubes, polyvinyl butyral, organic solvent and silane coupling agent is 1:1:0.25:12:0.05. The specific steps are as follows: 5g of polyvinyl pyrrolidone PVP-K30 is dispersed in 60mL of N,N-dimethylformamide by ultrasonic stirring, and then 5g of carboxylated multi-walled carbon nanotubes is slowly added, ultrasonic stirring is performed for 2h, and then 1.25g of polyvinyl butyral with a molecular weight of 170000-250000 is slowly added at a stirring speed of 1200r / min, and the temperature is maintained at 50°C and stirred for 2h to mix evenly, and then 0.25g of γ-aminopropyl triethoxysilane is slowly added to the above mixed solution, and after it is stirred evenly, it is allowed to stand for degassing to obtain the spinning solution.

[0035] (2) Using spinning solution as shell liquid and water as core liquid, the shell liquid and the core liquid are extruded into a water coagulation bath through a spinning head at a flow ratio of 30:15 mL / h to obtain a carbon nanotube hollow fiber membrane, which is then immersed, cleaned, and dried at room temperature.

[0036] The carbon nanotube hollow fiber membrane prepared in this embodiment has no cracks on the surface and cross-section, an outer diameter of 650 μm, and an inner diameter of 400 μm. The pore size test was performed using a capillary flow pore size analyzer: the average pore size of the carbon nanotube hollow fiber membrane prepared in this embodiment is 103 nm.

[0037] Example 2

[0038] (1) Preparation of spinning solution: The mass ratio of polyvinyl pyrrolidone, carbon nanotubes, polyvinyl butyral, organic solvent and silane coupling agent is 1:1:0.25:12:0.05. The spinning solution is prepared in the same manner as in Example 1, except that the silane coupling agent is replaced with γ-glycidyloxypropyltrimethoxysilane and the organic solvent is replaced with N,N-dimethylacetamide.

[0039] (2) Using spinning solution as shell liquid and water as core liquid, the shell liquid and the core liquid are extruded into a water coagulation bath through a spinning head at a flow ratio of 30:15 mL / h to obtain a carbon nanotube hollow fiber membrane, which is then dried at 100° C. after immersion cleaning.

[0040] The carbon nanotube hollow fiber membrane prepared in this embodiment has no cracks on the surface and cross-section, an outer diameter of 660 μm, and an inner diameter of 400 μm. The pore size test was performed using a capillary flow pore size analyzer: the average pore size of the carbon nanotube hollow fiber membrane prepared in this embodiment is 105 nm.

[0041] Example 3

[0042] (1) Preparation of spinning solution: The mass ratio of polyvinyl pyrrolidone, carbon nanotubes, polyvinyl butyral, organic solvent and silane coupling agent is 0.5:1:0.25:11:0.05. The spinning solution is prepared in the same manner as in Example 1, except that the carbon nanotubes are replaced with hydroxylated single-walled carbon nanotubes, and the amount of polyvinyl pyrrolidone and organic solvent (N,N-dimethylformamide) is reduced. The specific steps are as follows: 2.5g of polyvinyl pyrrolidone PVP-K30 is dispersed in 55mL of N,N-dimethylformamide by ultrasonic stirring, and then 5g of hydroxylated single-walled carbon nanotubes is slowly added, ultrasonic stirring is performed for 2h, and then 1.25g of polyvinyl butyral with a molecular weight of 170000-250000 is slowly added at a stirring speed of 1200r / min, and the temperature is maintained at 50°C and stirred for 2h to mix evenly, and then 0.25g of γ-aminopropyltriethoxysilane is slowly added to the above mixed solution, and after it is stirred evenly, it is allowed to stand and degas to obtain a spinning solution.

[0043] (2) Using spinning solution as shell liquid and water as core liquid, the shell liquid and the core liquid are extruded into a water coagulation bath through a spinning head at a flow ratio of 60:30 mL / h to obtain a carbon nanotube hollow fiber membrane, which is then dried at 80° C. after immersion cleaning.

[0044] The carbon nanotube hollow fiber membrane prepared in this embodiment has no cracks on the surface and cross-section, an outer diameter of 670 μm, and an inner diameter of 415 μm. The pore size test was performed using a capillary flow pore size analyzer: the average pore size of the carbon nanotube hollow fiber membrane prepared in this embodiment is 92 nm.

[0045] Example 4

[0046] (1) Preparation of spinning solution: The mass ratio of polyvinyl pyrrolidone, carbon nanotubes, polyvinyl butyral, organic solvent and silane coupling agent is 0.5:1:0.25:10:0.25. The spinning solution is prepared in the same manner as in Example 3, except that the carbon nanotubes are replaced with a mixture of carboxylated multi-walled carbon nanotubes and hydroxylated multi-walled carbon nanotubes in any proportion, and the amount of silane coupling agent (γ-aminopropyltriethoxysilane) is increased. The specific steps are as follows: 2.5g of polyvinyl pyrrolidone PVP-K30 is dispersed in 50mL of N,N-dimethylacetamide by ultrasonic stirring, and then a mixture of 2.5g of carboxylated multi-walled carbon nanotubes and 2.5g of hydroxylated multi-walled carbon nanotubes is slowly added, and ultrasonic stirring is performed for 2h, and then 1.25g of polyvinyl butyral with a molecular weight of 170000-250000 is slowly added at a stirring speed of 1200r / min, and the temperature is maintained at 50°C and stirred for 2h to mix evenly, and then 1.25g of γ-aminopropyltriethoxysilane is slowly added to the above mixed solution, and after it is stirred evenly, it is allowed to stand and degas to obtain a spinning solution.

[0047] (2) Using spinning solution as shell liquid and water as core liquid, the shell liquid and the core liquid are extruded into a water coagulation bath through a spinning head at a flow ratio of 60:40 mL / h to obtain a carbon nanotube hollow fiber membrane, which is then dried at 80° C. after immersion cleaning.

[0048] The carbon nanotube hollow fiber membrane prepared in the embodiment has no cracks on the surface and cross section, an outer diameter of 680 μm, and an inner diameter of 410 μm. Figure 1-3 As shown; the pore size test was performed using a capillary flow pore size analyzer: the average pore size of the carbon nanotube hollow fiber membrane prepared in this embodiment is 86nm; in addition, the carbon nanotube hollow fiber membrane has good flexibility and can be bent and twisted into a twisted shape without breaking, such as Figure 4 As shown, flexibility Figure 5 shown.

[0049] Example 5

[0050] (1) Preparation of spinning solution: The mass ratio of polyvinyl pyrrolidone, carbon nanotubes, polyvinyl butyral, organic solvent and silane coupling agent is 0.5:1:0.25:10:0.5. The spinning solution is prepared in the same manner as in Example 4, except that the mass ratio of γ-aminopropyltriethoxysilane is increased to 0.5.

[0051] (2) Using spinning solution as shell liquid and water as core liquid, the shell liquid and the core liquid are extruded into a water coagulation bath through a spinning head at a flow ratio of 80:40 mL / h to obtain a carbon nanotube hollow fiber membrane, which is then dried at 60° C. after immersion cleaning.

[0052] The carbon nanotube hollow fiber membrane prepared in this embodiment has no cracks on the surface and cross-section, an outer diameter of 680 μm, and an inner diameter of 415 μm. The pore size test was performed using a capillary flow pore size analyzer: the average pore size of the carbon nanotube hollow fiber membrane prepared in this embodiment is 78 nm.

[0053] Example 6

[0054] (1) Preparation of spinning solution: The mass ratio of polyvinyl pyrrolidone, carbon nanotubes, polyvinyl butyral, organic solvent and silane coupling agent is 0.5:1:0.25:10:0.5. The spinning solution is prepared in the same manner as in Example 5, except that polyvinyl pyrrolidone is replaced with PVP-K60, and the molecular weight of polyvinyl butyral is replaced with 90,000 to 120,000.

[0055] (2) Using spinning solution as shell liquid and water as core liquid, the shell liquid and the core liquid are extruded into a water coagulation bath through a spinning head at a flow ratio of 120:60 mL / h to obtain a carbon nanotube hollow fiber membrane, which is then dried at 60° C. after immersion cleaning.

[0056] The carbon nanotube hollow fiber membrane prepared in this embodiment has no cracks on the surface and cross-section, an outer diameter of 700 μm, and an inner diameter of 440 μm. The pore size test was performed using a capillary flow pore size analyzer: the average pore size of the carbon nanotube hollow fiber membrane prepared in this embodiment is 75 nm.

[0057] Comparative Example 1

[0058] (1) Preparation of spinning solution: The mass ratio of polyvinyl pyrrolidone, carbon nanotubes, polyvinyl butyral and organic solvent is 1:1:0.25:12. The spinning solution is prepared in the same manner as in Example 1, except that no silane coupling agent is added.

[0059] (2) Using spinning solution as shell liquid and water as core liquid, the shell liquid and core liquid are extruded into a water coagulation bath through a spinning head at a flow ratio of 30:15 mL / h to obtain a carbon nanotube hollow fiber membrane, which is then immersed, cleaned, and dried at room temperature.

[0060] The carbon nanotube hollow fiber membrane prepared in this comparative example has no cracks on the surface and cross-section, an outer diameter of 650 μm, and an inner diameter of 400 μm. The pore size test was performed using a capillary flow pore size analyzer: the average pore size of the carbon nanotube hollow fiber membrane prepared in this example is 108 nm.

[0061] The outer diameter, inner diameter and average pore size of the carbon nanotube hollow fiber membranes prepared in Examples 1-6 and Comparative Example 1 are summarized as shown in Table 1:

[0062] The carbon nanotube hollow fiber membranes prepared in the above Examples 1-6 and Comparative Example 1 were tested for flexibility, conductivity and tensile strength at break. The test results are shown in Table 1. The test method is as follows:

[0063] Flexibility test:

[0064] The flexibility of the carbon nanotube hollow fiber membrane was tested using the improved GB / T6742-86 paint film bending test method. The specific test process is as follows: the carbon nanotube hollow fiber was wound and bent on cylindrical rods of different diameters (from large to small). The membrane filaments did not break after bending and winding, and could be restored to their initial state after being released. Figure 5 As shown, the minimum shaft rod diameter that can be bent and wound without causing bending and fracture of the carbon nanotube hollow fiber membrane is used to characterize the flexibility of the membrane.

[0065] Conductivity test:

[0066] The resistance of the carbon nanotube hollow fiber membrane in dry and wet state at a certain length was tested by a multimeter, such as Figure 6 As shown, the conductivity of the membrane is then calculated according to the following formula:

[0067]

[0068] σ-conductivity (S / m);

[0069] L-length of membrane (m);

[0070] R-membrane resistance (Ω);

[0071] S-membrane cross-sectional area (m 2 )

[0072] Tensile test at break:

[0073] The tensile strength at break of the carbon nanotube hollow fiber membrane was tested using the HY / T 213-2016 method for determining the tensile strength at break of hollow fiber ultrafiltration / microfiltration membranes. The load at break of the carbon nanotube hollow fiber membrane was recorded using an electronic universal testing machine, and the tensile stress at break was calculated using the following formula:

[0074]

[0075] σ-tensile stress (MPa);

[0076] F-tensile load (N);

[0077] R-outer diameter of hollow fiber membrane (μm);

[0078] r-Inner diameter of hollow fiber membrane (μm)

[0079] Table 1 Test results of outer diameter, inner diameter, average pore size, flexibility, conductivity and tensile strength at break of carbon nanotube hollow fiber membrane

[0080]

[0081] The carbon nanotube hollow fiber membrane described in the present invention has strong flexibility, good electrical conductivity and good tensile strength. It can be seen from Table 1 that the carbon nanotube hollow fiber membrane described in Example 5 has the best flexibility and can be used in sewage treatment with relatively turbulent water flow or large hydraulic impact; the electrical conductivity in dry and wet states is also good, which provides a guarantee for adding electricity to improve other electrochemical enhanced membrane separation properties such as anti-membrane fouling in practical applications; by comparing Examples 1-6 with Comparative Example 1, it can be seen that the flexibility and tensile strength of the carbon nanotube hollow fiber membrane are significantly improved after the addition of silane coupling agent; in addition, the addition of silane coupling agent reduces the swelling of the membrane filaments and improves the conductivity of the membrane to a certain extent.

[0082] The above description is only a preferred embodiment of the present invention and does not limit the scope of implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A large-scale preparation method of a flexible carbon nanotube conductive hollow fiber membrane, characterized in that: The carbon nanotube conductive hollow fiber membrane contains a silane coupling agent, polyvinyl butyral, polyvinyl pyrrolidone and carbon nanotubes, wherein the mass ratio of the polyvinyl pyrrolidone, the carbon nanotubes, the polyvinyl butyral and the silane coupling agent is 0.2-1:1:0.15-0.5:0.05-0.5; the carbon nanotubes and the polyvinyl butyral are cross-linked by the silane coupling agent; The carbon nanotubes include one or more of carboxylated multi-walled carbon nanotubes, hydroxylated multi-walled carbon nanotubes, carboxylated single-walled carbon nanotubes, and hydroxylated single-walled carbon nanotubes; The preparation method comprises the following steps: (1) dispersing polyvinyl pyrrolidone, carbon nanotubes, polyvinyl butyral and a silane coupling agent in an organic solvent at a temperature of 30 to 60° C., stirring evenly and then standing to degas to obtain a spinning solution; (2) Wet spinning: The spinning solution is used as the shell liquid and water is used as the core liquid. The spinning solution and the core liquid are extruded into a water coagulation bath through a spinning head at a volume flow ratio of 1 to 3:

1. The obtained product is soaked, washed and then dried.

2. The preparation method according to claim 1, characterized in that: The silane coupling agent includes one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane, N-β-aminoethyl-γ-aminopropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and vinyl-tri(2-methoxyethoxy)silane.

3. The preparation method according to claim 2, characterized in that: The silane coupling agent is γ-aminopropyltriethoxysilane.

4. The preparation method according to claim 1, characterized in that: The molecular weight of the polyvinyl pyrrolidone is 8000-1300000; the molecular weight of the polyvinyl butyral is 25000-2000000.

5. The preparation method according to claim 4, characterized in that: The molecular weight of the polyvinyl pyrrolidone is 40,000 to 58,000; the molecular weight of the polyvinyl butyral is 170,000 to 250,000.

6. The preparation method according to claim 1, characterized in that: The organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

7. The preparation method according to claim 1, characterized in that: The drying is performed at a temperature not higher than 100°C.

8. Application of the flexible carbon nanotube conductive hollow fiber membrane prepared by the preparation method according to any one of claims 1 to 7, characterized in that: Applied to water treatment with negatively charged pollutants.

9. The use according to claim 8, characterized in that: The water treatment with negatively charged pollutants includes industrial wastewater treatment or drinking water purification.